An organophosphine oxide redox shuttle additive that delivers long-term overcharge protection for 4 V lithium-ion batteries1. Issue 20 (28th May 2015) - Huang, Jinhua; Azimi, Nasim; Cheng, Lei; Shkrob, Ilya A.; Xue, Zheng; Zhang, Junjie; Dietz Rago, Nancy L.; Curtiss, Larry A.; Amine, Khalil; Zhang, Zhengcheng; Zhang, Lu
<x xml:space="preserve">Abstract</x> Redox shuttle additives are used to protect Li-ion batteries from overcharge.